Clinical associations of an updated medication effect score for measuring diabetes treatment intensity. (December 2021) - Alexopoulos, Anastasia-Stefania; Yancy, William S; Edelman, David; Coffman, Cynthia J; Jeffreys, Amy S; Maciejewski, Matthew L; Voils, Corrine I; Sagalla, Nicole; Barton Bradley, Anna; Dar, Moahad; Mayer, Stéphanie B; Crowley, Matthew J
Objectives: The medication effect score reflects overall intensity of a diabetes regimen by consolidating dosage and potency of agents used. Little is understood regarding how medication intensity relates to clinical factors. We updated the medication effect score to account for newer agents and explored associations between medication effect score and patient-level clinical factors. Methods: Cross-sectional analysis of baseline data from a randomized controlled trial involving 263 Veterans with type 2 diabetes and hemoglobin A1c levels ≥8.0% (≥7.5% if under age 50). Medication effect score was calculated for all patients at baseline, alongside additional measures including demographics, comorbid illnesses, hemoglobin A1c, and self-reported psychosocial factors. We used multivariable regression to explore associations between baseline medication effect score and patient-level clinical factors. Results: Our sample had a mean age of 60.7 ( SD  = 8.2) years, was 89.4% male, and 57.4% non-White. Older age and younger onset of diabetes were associated with a higher medication effect score, as was higher body mass index. Higher medication effect score was significantly associated with medication nonadherence, although not with hemoglobin A1c, self-reported hypoglycemia, diabetes-related distress, or depression. Discussion: We observed several expected associations between an updated medication effect score and patient-level clinical factors. These associations support the medication effect score as an appropriate measure of diabetes regimen intensity in clinical and research contexts.